Α-Tocopherol, β-carotene, lutein, squalene and secoiridoids in seven monocultivar Italian extra-virgin olive oils. (4th July 2017) - Ambra, Roberto; Natella, Fausta; Lucchetti, Sabrina; Forte, Valentina; Pastore, Gianni
Abstract: Fatty acids and bioactive lipophilic and hydrophilic compounds (tocopherols, β-carotene, lutein, squalene, total polyphenols and secoiridoids) in monocultivar Italian extra-virgin olive oil (EVOO) samples produced from the Leccino cultivar and six other yet uncharacterised cultivars (Rustica, Carpinetana, Dritta, Gentile di Chieti and Intosso) were analysed, also taking into account the effect of the type of decanter used for the oil extraction. Significant differences among cultivars were found for α-tocopherol and squalene, but not for carotenoids. Among phenols, cultivars significantly influenced oleuropein and ligstroside aglycones contents, but not those of the dialdehydic form of decarboxymethyl elenolic acid linked neither to tyrosol nor hydroxytyrosol. As previously reported, phenol is quantitatively affected by the type of decanter used for oil extraction. Accordingly, we found that the two-phases decanter preserved in the oil 1.5 times more phenolic compounds as compared with three-phases, whereas it did not influence the amount of lipophilic compounds. Moreover, our data statistically support the finding that type of decanter affects phenols also qualitatively. In fact, the two-phases decanter preferably preserved more the hydroxytyrosol secoiridoid derivatives than the tyrosol ones. Our results from one hand characterise for the first time oils previously unreported, from the other give some new indications on the relative role of factors relevant for the achievement of biologically active extra-virgin oil, i.e. the cultivar and technological ones.